Revitalizing the Role of Child Protection Institutions in Preventing Child Marriage in South Sulawesi: A Maqashid al-Syari‘ah Perspective - Syahabuddin Syahabuddin; Mustafa Mustafa; Hamzah Hamzah; Firdaus Firdaus; Muhammad Suyuthy R; Ma’adul Yaqien Makkarateng (Al-Mazaahib: Jurnal Perbandingan Hukum, 2025)
Child marriage in South Sulawesi remains a critical issue in public health and social development, despite previous studies on recent legal reforms. This research fills an academic gap by comprehensively evaluating the performance of the Child Protection Agency (LPA) in South Sulawesi through the lens of maqashid al-syari’ah, aiming to assess the effectiveness of the LPA and to formulate optimization strategies for its role in the region. Employing a mixed-methods approach—combining surveys and in-depth interviews—the findings reveal that community perceptions of LPA services (counseling, advocacy, and relevance) are generally positive. However, qualitative analysis using Sutrisno’s effectiveness theory uncovers a significant gap: the perceived success reflects service accessibility rather than substantive social impact. The core findings indicate that the effectiveness of the LPA in South Sulawesi is constrained by difficulties in reaching informal communities and the absence of a systematic early detection system for at-risk children. The implications of this analysis highlight the need for substantive strategic shifts grounded in maqashid al-syari’ah (emphasizing hifz al-nafs, hifz al-‘aql, and hifz al-nasl). These strategic shifts include enacting Regional Regulations (PERDA), expanding outreach by engaging religious and community leaders, strengthening early detection through cross-sectoral collaboration, and empowering local governments. Such comprehensive strategic reforms are essential to enhance the effectiveness of the LPA in South Sulawesi and to ensure greater protection for children. Perkawinan anak di Sulawesi Selatan tetap menjadi isu krusial dalam kesehatan masyarakat dan social, meskipun telah ada penelitian sebelumnya terhadap reformasi hukum terbaru. Penelitian ini mengisi kesenjangan akademik dalam mengevaluasi kinerja lembaga perlindungan anak (LPA) di Sulawesi selatan secara komprehensif melalui pendekatan maqashid al-syari’ah, dengan tujuan menilai efektivitas LPA di Sulawesi selatan serta merumuskan strategi optimalisasi peran LPA di Sulawesi selatan. Menggunakan pendekatan mixed methods, dengan metode survei dan wawancara mendalam. Hasil survei menunjukkan persepsi positif masyarakat terhadap layanan LPA (konseling, advokasi, dan relevansi). Namun, analisis kualitatif dengan menggunakan teori efektivitas Sutrisno mengungkapkan adanya kesenjangan signifikan, keberhasilan yang dirasakan lebih merefleksikan aksesibilitas layanan daripada dampak sosial yang substantif. Temuan utama menunjukkan bahwa efektivitas LPA di Sulawesi selatan terhambat oleh kesulitan menjangkau komunitas informal serta ketiadaan sistem deteksi dini yang sistematis bagi anak-anak berisiko. Implikasi dari analisis ini menekankan perlunya pergeseran strategi substantif yang berlandaskan maqashid al-syari’ah, (menekankan hifz al-nafs, hifz al-‘aql, dan hifz al-nasl). Pergeseran tersebut mencakup pembentukan Peraturan Daerah (PERDA), perluasan jangkauan dengan melibatkan tokoh agama dan masyarakat, penguatan deteksi dini melalui kolaborasi lintas sektor, serta pemberdayaan pemerintah daerah. Pergeseran strategis yang komprehensif ini diperlukan untuk meningkatkan efektivitas LPA Sulawesi selatan dan memastikan perlindungan yang lebih optimal bagi anak-anak.